Can the 17th century Latvian dictionaries be trusted in the search for old meanings? - Trumpa, Anta (Vilnius University Open Series, 2018)
[full article and abstract in Lithuanian; abstract in English] This paper analyzes two of the 17th century Latvian dictionaries – the Lettus by Georgius Mancelius and the dictionary manuscripts of Christopher Fürecker from the end of the 17th century. The task of the paper: based on the experience gained working with the Historical Dictionary of the Latvian Language, to try and determine how reliable the translations of the meanings found in the 17th century dictionaries are and to what extent can they be used for determining the meanings in the historical dictionary. Examples included in the Historical Dictionary of the Latvian Language are divided into several groups depending on the following aspects: 1) Whether a word of the Latvian language or its German translation is or is not commonly used nowadays; 2) Whether the meaning of these words have or have not changed to the present day. Within each group, one or more examples are considered, including a possible explanation of the meaning of the word in the Historical Dictionary of the Latvian Language. Based on the examples given, it was concluded that, despite some unequivocal mistakes of explanation of the meaning, in most cases, the explanations of the meanings of the words in the dictionary of G. Mancelius and the manuscripts of the dictionary of K. Fürecker are given correctly, as evidenced by the use of the corresponding words in the related texts. It is more difficult to judge in cases when one must rely solely on dictionaries, the German translations of words, because the German language has also changed significantly since the 17th century; the old Latvian dictionaries contain obsolete words specific to the Baltic German language. In such cases, the historical dictionaries of the German language, dialect dictionaries, as well as the dictionary of the Baltic-German language, are helpful in understanding the word meanings. Consequently, many translations that originally seem like mistakes of the authors of the 17th century dictionaries, however, turn out to be correct after a more in-depth study and a careful analysis of the linguistic circumstances of that respective period.